Awareness in severe Alzheimer's disease: a systematic review. (3rd April 2021) - O'Shaughnessy, N. J.; Chan, J. E.; Bhome, R.; Gallagher, P.; Zhang, H.; Clare, L.; Sampson, E. L.; Stone, P.; Huntley, J.
Abstract: Objective: There is limited understanding about how people in the severe stages of Alzheimer's disease (AD) experience and demonstrate awareness. We synthesised all available evidence with the aim of understanding how awareness is preserved or impaired in severe AD and what evidence there is for different levels of awareness according to the levels of awareness framework. Method: A systematic search of the following databases: Embase, PsycINFO, MEDLINE and Web of Science was carried out. A narrative synthesis and analysis was conducted of all included studies. All studies were assessed for quality using the AXIS and CASP tools. Results: Our findings suggest that lower level sensory awareness is relatively maintained in severe AD. Findings for higher level awareness are variable and this may be related to the diversity of methods that have been used to explore awareness in these circumstances. Conclusion: Awareness is complex, heterogeneous and varies significantly between individuals. Environmental and contextual factors have a significant impact on whether awareness is observed in people with severe AD. Adaptation of the environment has the potential to facilitate the expression of awareness while education of caregivers may increase understanding of people with severe AD and potentially improve the quality of care that is received.